Real-World experience of interictal burden and treatment in migraine: a qualitative interview study - Siu Hing Lo; Katy Gallop; Timothy Smith; Lauren Powell; Karissa Johnston; Lena T. Hubig; Emma Williams; Vladimir Coric; Linda Harris; Gilbert L’Italien; Andrew J. Lloyd (The Journal of Headache and Pain, 2022)
Abstract Background The debilitating nature of migraine attacks is widely established; however, less is known about how the interictal burden (i.e., how patients are affected in-between migraine episodes) of migraine impacts on patients’ health-related quality of life (HRQL). Acute and preventive treatments may lift the burden of the disease, but they often have unwanted side effects and limited effectiveness. The objective of this study was to understand the interictal burden of migraines, from the patient perspective, and to explore patient experience with migraine treatments. Methods Participants (n=35) with a self-reported diagnosis of migraine were recruited in the US, UK and Canada, including a subgroup of patients who had taken calcitonin gene-related peptide monoclonal antibody (CGRP mAb) treatment for at least three months. Participants completed a background questionnaire, followed by a semi-structured interview via telephone or video call. The interviews explored patients’ migraine symptoms, perception of interictal burden and treatment experience. The interview transcripts were analysed using thematic analysis. Results The most reported migraine symptom was migraine pain, followed by aura, sensory sensitivity and nausea. Most participants reported interictal impact on HRQL, lifestyle changes they made to avoid triggers or in anticipation of an attack, impacts on work, career, daily activities and relationships. Emotional impacts were reported by all participants, including anger, depression, anxiety and hopelessness. Many participants who took preventive treatments reported improvements in HRQL and functioning but still experienced breakthrough attacks. Among patients who took CGRP mAbs, participants noted varying consistency of treatment effectiveness between treatment administrations. Conclusion This study detailed the additional HRQL impact of migraine in-between migraine attacks and described the unmet need for effective treatment options to prevent and mitigate migraine attacks.